DEGRADASI INTEGRITAS PUBLIK POLITISI DALAM PENGGUNAAN ANGGARAN DANA DESA BUKIT PAMEWA KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Yani, Ren; Hospita, Wira; Asrinaldi, Asrinaldi; Zetra, Aidinil (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
Public integrity and politicians will be seen when they are faced with public policies concerning the management of state assets. This is because, when the public official is faced with conflicting obligations, but is able to provide solutions to the exclusion of personal or group interests. The integrity of public politicians, good governance will be created. The problem is, currently the public of politicians with integrity are rarely found, the many conflicts of interest make public officials waste their spending on the state, ultimately resulting in inefficient and low quality public policies. The case that occurred in the Bukit Pamewa Village government, Mentawai District, reflects that there has been a degradation of the integrity of the public politicians. Village funds budget (ADD) which should be used for the welfare of the community through development, was apparently not implemented in accordance with the program or activity plan. The results of this study found that abuse of public officials' authority over the use of public funds carried out by the Village Head together with his equipment was seen in the determination of the amount and budget allocator there was always the interest of the Village Chief who was accommodated by the Village Apparatus. This study uses a qualitative method, where the theory of budgetary politics and elite theory is used as a knife for analysis.